The Upcoming Role for Nursing and Assistive Robotics: Opportunities and Challenges Ahead - Christoforou, Eftychios G.; Avgousti, Sotiris; Ramdani, Nacim; Novales, Cyril; Panayides, Andreas S. (Frontiers in Digital Health, 2020)
As an integral part of patient care, nursing is required to constantly adapt to changes in the healthcare system, as well as the wider financial and societal environment. Among the key factors driving these changes is the aging of population. Combined with an existing shortage of nursing and caregiving professionals, accommodating for the patients and elderly needs within hospitals, elderly-care facilities and at home, becomes a societal challenge. Technological solutions evolved in response to these developments include the nursing and assistive robotics. These emerging technologies are reviewed to portray their current status and highlight their potential, while identifying existing challenges and limitations with direct impact on future developments. A survey conducted to investigate relevant issues from a nursing professionals’ perspective is presented.